Case series of carbapenemase-producing Enterobacteriaceae osteomyelitis: Feel it in your bones. (December 2020) - Davido, B.; Noussair, L.; Saleh-Mghir, A.; Salomon, E.; Bouchand, F.; Matt, M.; Lawrence, C.; Bauer, T.; Herrmann, J.L.; Perronne, C.; Gaillard, J.L.; Rottman, M.; et al.
Highlights: Carbapenemase-producing Enterobacteriaceae (CPE) osteomyelitis is a rare condition. Treatment of CPE osteomyelitis is complex and mainly based on triple antimicrobial therapy. CPE osteomyelitides are mostly associated with functional status disability. Abstract: Objectives: Limited data have been reported regarding osteomyelitis due to carbapenemase-producing Enterobacteriaceae (CPE), including co-infections with extended-spectrum β-lactamase (ESBL)-producing micro-organisms. Methods: We conducted a retrospective study in a reference centre for bone and joint infections from 2011 to 2019 among patients infected with CPE. Results: Nine patients (mean age 46.8 ± 16.6 years), including three with infected implants, were identified. Infections were mostly polymicrobial ( n = 8/9), including Staphylococcus aureus ( n = 6/9). CPE were mainly OXA-48-type, associated with ESBL-producing Enterobacteriaceae ( n = 8/9), of which 5/9 isolates were Klebsiella pneumoniae . Control of the infection was achieved in seven cases. Conclusions: CPE osteomyelitides are essentially polymicrobial and fluoroquinolone-resistant infections, highlighting the need for efficient surgery with implant removal.